2018
DOI: 10.5897/jphe2018.1070
|View full text |Cite
|
Sign up to set email alerts
|

Investigating risk factors associated with the persistence of malaria in the Obang valley, North West Region, Cameroon

Abstract: Malaria interventions-vector control using long-lasting insecticidal nets (LLINs) or indoor residual spraying, chemoprevention and case management including diagnosis and treatment of infections-are highly effective and affordable. These interventions have led to a significant reduction in malaria prevalence, and a marked decline in morbidity and mortality associated. Despite these increasing control efforts, this parasitic disease is still persisting in most African countries. The aim of this study was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Majority of the study population (86.6%) were aware about the cause of malaria whereas their awareness about the cause of typhoid was below average (48.0%). Therefore, the study population were well sensitised about malaria in accordance with Gangue et al (2018), although users of ITNs were slightly exposed to malaria risk factors. This might be due to their outdoor activities without taking preventive measures against mosquito bites and the degree of household crowding (Ferrari et al, 2016;Gangue et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Majority of the study population (86.6%) were aware about the cause of malaria whereas their awareness about the cause of typhoid was below average (48.0%). Therefore, the study population were well sensitised about malaria in accordance with Gangue et al (2018), although users of ITNs were slightly exposed to malaria risk factors. This might be due to their outdoor activities without taking preventive measures against mosquito bites and the degree of household crowding (Ferrari et al, 2016;Gangue et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study population were well sensitised about malaria in accordance with Gangue et al (2018), although users of ITNs were slightly exposed to malaria risk factors. This might be due to their outdoor activities without taking preventive measures against mosquito bites and the degree of household crowding (Ferrari et al, 2016;Gangue et al, 2018). In addition, living in homes with bushes around was a malaria risk factor just as late acquisition of mosquito net and its utilisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e authors in [70] have discussed safety applications related to AI in those domains where deep reinforcement learning is applied to the control of automatic mobile robots. An investigation of the risk associated with malaria infection to identify those bottlenecks in different malaria elimination techniques is discussed in [71]. Other relevant studies can be found in [72][73][74].…”
Section: Related Workmentioning
confidence: 99%